CHRONIC NEUROPATHIC PAIN IN POST COVID PATIENTS RELATION WITH DISEASE SEVERITY - AWAN, NUS; ISHAQ, A; NAZIR, M; KHALID, L; IQBAL, MM; MUGHAL, ZM (Biological and Clinical Sciences Research Journal, 2024)
Post-COVID syndrome, also known as post-acute sequelae of SARS-CoV-2 infection, has been associated with various long-term effects, one of which is neuropathic pain. This condition is characterized by chronic pain arising from nerve injury and has been observed in many patients recovering from COVID-19, potentially correlating with the severity of the initial infection. Objective: The study aimed to compare the prevalence and types of neuropathic pain in post-COVID patients and investigate the correlation between chronic neuropathic pain and the severity of the initial COVID-19 infection. Methods: This prospective observational study was conducted at the Department of Medicine, SKBZ/CMH Hospital Muzaffarabad, AJK, from February to August 2024. One hundred fifty post-COVID patients were enrolled, categorized into mild/moderate and severe groups (50 patients each). Neuropathic pain was assessed using the Neuropathic Pain Scale (NPS) at three and six months post-infection. Statistical analysis was performed using Analysis of Variance (ANOVA) to compare mean responses, with p-values < 0.05 considered statistically significant. Results: Out of 150 patients, 53.3% (80 patients) reported experiencing chronic neuropathic pain. Neuropathic pain was more prevalent in patients who had severe COVID-19 symptoms, with 65% of severe cases reporting pain, compared to 40% of mild/moderate cases. The mean NPS score was significantly higher in severe cases (6.8 ± 1.2) compared to mild/moderate cases (4.3 ± 1.0), with a p-value of < 0.01, indicating a strong association between the severity of the initial infection and the subsequent development of neuropathic pain. Conclusion: There is a higher incidence and severity of chronic neuropathic pain in post-COVID patients, particularly those who experienced severe disease manifestations. Early identification and targeted pain management strategies are essential for mitigating the long-term impact of neuropathic pain in these patients.